PD Behaviors of Monoester Insulating Oil under Different Moisture Contents - Abdul Rajab; Motoo Tsuchie; Masahiro Kozako; Masayuki Hikita; Takashi Suzuki (Universitas Ahmad Dahlan, 2018)
One of the problems encounters in implementing vegetable oils (natural esters) as a transformer insulating oil is their viscosity which is high. To address this problem, monoester derived from vegetable oil was introduced. This paper deals with partial discharge (PD) behaviors of dry and moist samples of a monoester type insulating oil, palm fatty acid ester (PFAE), under AC high voltage utilizing a needle plane electrode configuration. Variations of average PD charge and PD number against the variation of voltage application, as well as their polarity discrimination under both dry and moist sample conditions are analyzed. PD pulses phase distributions of both dry and moist sample oils are elaborated. Finally, a mechanism of the water molecules effect on PD behavior is proposed based on experimental results and shown schematically.